Parental Androids - Valeria Franceschi; Valentina Romanzi (Iperstoria, 2023)
About forty years ago, feminist scholars formulated several independent definitions of an ethics of care (Gilligan 1982; Ruddick 1989; Noddings 1984), suggesting the need to reframe human collective and personal interactions. However, care theory fails for the most part to consider the lived experiences and the needs of marginalized subjects (Gary 2022). This study observes care theory from a linguistic perspective in three audio-visual texts featuring examples of non-normative care. The sci-fi TV series Star Trek: The Next Generation, Battlestar Galactica, and Raised by Wolves will be considered, with a focus on androids acting as caregivers. The linguistic analysis, following a Discourse-Historical Approach (DHA), will focus on discursive strategies relating to the parties involved, their relational ties, care behaviors, and the androids’ adequacy as caretakers. The emerging perspectives may be mapped onto current discourse on minority groups’ access to fostering or adoption and their reproductive rights.